2007
DOI: 10.1038/sj.bjc.6603955
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of human papillomavirus antibodies in young female subjects in England

Abstract: Sera from 1483 female subjects in England aged 10 -29 years were tested. The age-standardised seroprevalence was 10.7% (95% confidence intervals 9.0 -12.3) for human papillomavirus (HPV) 6, 2.7% (1.8 -3.6) for HPV 11, 11.9% (10.2 -13.6) for HPV 16, 4.7% (3.5 -5.8) for HPV 18, Infection with human papillomavirus (HPV) types identified as 'high-risk' is a pre-requisite for developing cervical cancer (Munoz et al, 2003). HPV types 16 and 18 are associated with 70% of cervical cancers worldwide (Munoz et al, 2003)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 17 publications
(30 reference statements)
3
31
1
Order By: Relevance
“…There is recent evidence that ELISA is a lesssensitive method than the bead-based multiplex assay used in our study (Waterboer et al, 2005). In general, we can conclude that the baseline seroprevalence figures for all HPV types in our study were higher than reported previously (Lehtinen et al, 2006;Rama et al, 2006;Jit et al, 2007;Skjeldestad et al, 2008;Wang et al, 2008). When the more stringent (400 MFI) cut-off value for L1 antibodies was used, seroprevalence declined by [15][16][17][18][19][20]in particular,seroprevalence of HPV 16 (20 %) and HPV 18 (8 %) was in line with earlier reports (Viscidi et al, 1997;af Geijersstam et al, 1998;Stone et al, 2002).…”
Section: S Syrjä Nen and Others 1522contrasting
confidence: 55%
“…There is recent evidence that ELISA is a lesssensitive method than the bead-based multiplex assay used in our study (Waterboer et al, 2005). In general, we can conclude that the baseline seroprevalence figures for all HPV types in our study were higher than reported previously (Lehtinen et al, 2006;Rama et al, 2006;Jit et al, 2007;Skjeldestad et al, 2008;Wang et al, 2008). When the more stringent (400 MFI) cut-off value for L1 antibodies was used, seroprevalence declined by [15][16][17][18][19][20]in particular,seroprevalence of HPV 16 (20 %) and HPV 18 (8 %) was in line with earlier reports (Viscidi et al, 1997;af Geijersstam et al, 1998;Stone et al, 2002).…”
Section: S Syrjä Nen and Others 1522contrasting
confidence: 55%
“…This collection has been widely used in epidemiologic studies (see references 6,11,20,31,33, and 34 for examples). One disadvantage of this collection is that in order to preserve anonymity, few details regarding the individuals from whom the sera were collected are available.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of HPV seroprevalence studies have been carried out in women from high-resource countries (3,6,(8)(9)(10)(11)(12)(13)(14). Few studies have focused on low-resource areas, such as Central and South America (7,(15)(16)(17), Asia (5,18) or Africa (19), where the highest HPV DNA prevalence in the world can be found, notably among middleaged women (20).…”
Section: Introductionmentioning
confidence: 99%